A scrambling and encryption algorithm for selective block of identification photo - Qingling Jiang; Wu Zeng; Weihua Ou; Renhong Xu (International Conference on Wireless Communications and Signal Processing, 2016)
As identification photo being a significant part of personal information security, the encryption of identification photo has become a frontier subject. The encryption of identification photo, different from common image encryption, mainly focuses on the human facial region. Therefore, the key point is to distinguish the face details and background details accurately and to design an encryption algorithm with huge key space and sensitivity key. In this paper, we proposes an image algorithm for color identification photo by multi-layer block scrambling in frequency domain. After dividing the image into blocks and detecting the human facial region, we encrypt the facial region in frequency domain. In comparison with the commonly used image encryption algorithm, the experimental result shows that the proposed algorithm requires less amount of calculation, while simultaneously provides larger algorithm key space and more sensitive key.